Komposisi Ekstrak Stevia (Stevia rebaudiana) Terhadap Karakteristik Sirup Bit (Beta vulgaris L.) - Elvi Fitriani Simarmata; Maria Marina Herawati; Alfred Jansen Sutrisno; Yoga Aji Handoko (Jurnal Penelitian Pertanian Terapan, 2019)
Beetroots are a type of tubers with a distinctive purplish red color and are beneficial for health with a high amount of betasianin as an antioxidant, as well as its use in preventing infection. But the beetroot is less liked by the public because of the strong enough earthy taste, so it is necessary to do new innovations for the product to be accepted by the community, one of which is the functional beet syrup drink. To create a preferred flavor, the addition of other food additives and sweetener stevia which has a sweetness level of 200-300 times that of sugar and includes non-calorie sweeteners is done. This study aims to analyze the best concentration of stevia extract on the sweetness level and beetroot characteristics and determine the level of panelists' preference for beetroot syrup (Beta vulgaris L.) with organoleptic tests. This research was conducted with a randomized block design (RBD), the data were analyzed by variance (ANOVA), if the data obtained were significantly different, the DMRT would be further tested at 5% level. The results showed that the highest betasianin was in the SBS15 treatment (31.74 mg / l), the highest total dissolved solids was in the SBS treatment (3.25ÂºBrix), the highest pH was in the SBS15 treatment (4.22), the highest vitamin C was in the SBS15 treatment (11.66 mg ascorbic acid / 10 ml). Organoleptic results showed that beet syrup with the addition of stevia extract of 6% was the most preferred sample by panelists.Â